Use and adequacy of non‐pregnancy diagnosis in cow. Which future?. (10th August 2022) - Gnemmi, Giovanni Maria; Maraboli, Cristina Vittoria A.; Gnemmi, Benedetta; Saleri, Roberta; De Rensis, Fabio
Abstract: In cattle, early detection of gestation is very important from an economic and management point of view in all types of farming. However, due to the poor efficiency of oestrous detection, it is essential to determine non‐pregnant cows as early as possible, in order to minimize the inter‐insemination interval, thus de facto, reducing herd open days. Direct and indirect gestation diagnostic methods have been developed with the aim of improving the reproductive performance of the herd. Today, the most accurate method for making an early diagnosis of gestation from 28 to 30 days post‐insemination is B‐mode ultrasound. In recent years, indirect methods have included techniques that allow non‐pregnant cows to be identified with a minimum margin of error, the most widely utilized of which is the colour Doppler. This technique is rapidly becoming established for the diagnosis of non‐pregnancy, which allows for the identification of non‐pregnant animals earlier compared with the pregnancy diagnosis. Some limitations of this technique in dairy cow have been presented.